Life-table and intrinsic rate of increase of seed beetle (Caryedon serratus) on groundnut at different temperatures - PRASAD, T V; NANDAGOPAL, V; GEDIA, M V; SAVALIYA, S D (The Indian Journal of Agricultural Sciences, 2011)
The age-specific survival and fecundity rates of groundnut seed beetle (Caryedon serratus Olivier) at different temperatures (25, 30, 35 and 40°C) in the laboratory on groundnut (Arachis hypogaea L.) were studied to estimate the dependence of the intrinsic rate of increase on temperature. Results indicated that the fecundity, survival rates and developmental time of C. serratus were different at different temperatures. The fecundity of C. serratus reared at 25°C was highest and decreased with the increase in temperature. Net reproductive rate and mean length of generation also decreased with the increase in temperature. Net reproductive rate varied from 159.07 viable eggs/female at 25°C to 101.94 eggs/female at 40°C and mean generation time varied from 166.52 days at 25°C to 59.31 days at 40°C. The intrinsic rate of increase (rm), the innate capacity for increase (rc), and finite rate of increase (λ) increased with increase in temperature from 25 to 40°C. Intrinsic rate of increase (rm), varied from 0.0316 females/female/day at 25°C to 0.0784 females/female/day at 40°C. The intrinsic rate of natural increase (rm) at 40°C was 2.48 times higher than that at 25°C. The shorter generation time and higher intrinsic rate of increase shortened the population doubling time of C. serratus to 8.96 days at 40°C compared to 21.94 days at 25°C.